2010
DOI: 10.1063/1.3457843
|View full text |Cite
|
Sign up to set email alerts
|

Large critical magnetic field and tunneling anomaly behavior of superconducting carbon-coated Sn nanorods and nanoparticles

Abstract: Ac susceptibility studies of a superconducting gallium nanocomposite: Crossover in the upper critical field line and activation barriers Evidence that the upper critical field of Nb3Sn is independent of whether it is cubic or tetragonal Appl. Phys. Lett. 99, 122507 (2011); 10.1063/1.3643055Quasiperiodic superconducting V/Zr multilayers: critical magnetic fields and crossover Low Temp.The arc-discharge process is usually used to synthesize some kinds of metal nanocrystals or nanoparticles all with high melting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The T C (15.1 K) of the as-prepared NbN nanoparticles is slightly less than that of 17 K for a bulk NbN. The size distribution (5-15 nm) of the NbN nanoparticles obtained in this work is comparable with the corresponding temperature-dependent coherent length, leading to the experience suppression in the superconducting transition temperature [18,19]. The superconducting transition temperature T c of the nanoparticles as a function of their size d has been studied both theoretically and experimentally.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…The T C (15.1 K) of the as-prepared NbN nanoparticles is slightly less than that of 17 K for a bulk NbN. The size distribution (5-15 nm) of the NbN nanoparticles obtained in this work is comparable with the corresponding temperature-dependent coherent length, leading to the experience suppression in the superconducting transition temperature [18,19]. The superconducting transition temperature T c of the nanoparticles as a function of their size d has been studied both theoretically and experimentally.…”
Section: Resultsmentioning
confidence: 59%
“…After the chamber was evacuated to 5.8 Â 10 À 3 Pa, a mixture of H 2 (0.04 MPa), Ar (0.16 MPa) and N 2 (0.48 MPa) was introduced into the chamber. Then the arc was ignited and the current was maintained at 100 A for 2 h. After being passivated in 0.12 MPa N 2 for 24 h, products were collected from the water-cooling copper crucible in front of the target, which was different from the conventional water-cooling top and chamber wall [16][17][18][19].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a similar behavior was also observed in a graphene-metal hybrid [36] or a Josephson junction array [37]. For the present Sn@CNT NRs, Josephson junction of Sn/CNT/Sn layered structure and the weakly linked nanocapsules are essential in nanoscale [14].…”
Section: Superconductivity Of Sn@cnt Nrs Below T Cmentioning
confidence: 49%
“…It has been reported that the superconductivity of carbon-coated Sn@C NCs will be destroyed as the size decreases down to 40 nm. However, it has also been demonstrated for the carbon-coated Sn nanorods with diameter of 50 nm and length of 200 nm, the critical magnetic field is almost 25 times higher than that of bulk Sn [14]. Large electrical current was also detected for MWCNTs encapsulated Sn nanowire, which can raise a local heating and in turn suppresses the superconductivity [15].…”
Section: Introductionmentioning
confidence: 97%